OMEGA, a randomized, placebo-controlled trial to test the effect of highly purified omega-3 fatty acids on top of modern guideline-adjusted therapy after myocardial infarction - Rauch, Bernhard; Schiele, Rudolf; Schneider, Steffen; Diller, Frank; Victor, Norbert; Gohlke, Helmut; Gottwik, Martin; Steinbeck, Gerhard; Del Castillo, Ulrike; Sack, Rudolf; Worth, Heinrich; Katus, Hugo; et al. (Circulation, 2010)
Background— - - There is no randomized, double-blind trial testing the prognostic effect of highly purified omega-3 fatty acids in addition to current guideline-adjusted treatment of acute myocardial infarction. - - Methods and Results— - - OMEGA is a randomized, placebo-controlled, double-blind, multicenter trial testing the effects of omega-3-acid ethyl esters-90 (1 g/d for 1 year) on the rate of sudden cardiac death in survivors of acute myocardial infarction, if given in addition to current guideline-adjusted treatment. Secondary end points were total mortality and nonfatal clinical events. Patients (n=3851; female, 25.6%; mean age, 64.0 years) were randomized in 104 German centers 3 to 14 days after acute myocardial infarction from October 2003 until June 2007. Acute coronary angiography was performed in 93.8% and acute percutaneous coronary intervention in 77.8% of all patients. During a follow-up of 365 days, the event rates were (omega and control groups) as follows: sudden cardiac death, 1.5% and 1.5% (P=0.84); total mortality, 4.6% and 3.7% (P=0.18); major adverse cerebrovascular and cardiovascular events, 10.4% and 8.8% (P=0.1); and revascularization in survivors, 27.6% and 29.1% (P=0.34). - - Conclusions— - - Guideline-adjusted treatment of acute myocardial infarction results in a low rate of sudden cardiac death and other clinical events within 1 year of follow-up, which could not be shown to be further reduced by the application of omega-3 fatty acids. - - Clinical Trial Registration— - - URL: http://www.clinicaltrials.gov. Unique identifier: NCT00251134.